DESAIN DAN ANALISIS UPHEAVAL BUCKLING UNTUK PIPA PENYALUR CAIRAN DAN GAS DI INDONESIA - Ricky, Leo
Pipelines are the critical supporting facility in the oil and gas industry. Therefore the manufacture of good pipeline design is a major need. This final project designed a 7.9 km liquid pipeline and a 13.2 km gas pipeline. Both pipelines expected to pass through the river area, thus several analyses were needed to ensure stability when passing through the river area. There were several stages in the design process in this final project, First, the selection of pipe layers (Corrosion Resistance Alloy, Corrosion Coating, and Pipe Material), the selection of wall thickness based on BS EN ISO 218091: 2011, and the design of the pipeline wall thickness referred to ASME B31.4 design standards for liquid pipes, ASME B31.8 for gas pipes, and ASME 36.10 for the selection of final pipe.Furthermore, for the pipeline passing through the river area, the stability was calculated by referring to the DNV RP-E305 design standard. If the pipe is unstable, a cube-shaped concrete weight design will be placed at both ends of each pipe that passes through the river. Then several analyzes were carried out to ensure that the pipelines did not fail under operating conditions, which were the thermal end expansion analysis, pipe stress analysis using Ceasar II Software, and Upheaval Buckling analysis referred to OTC 6335. Based on calculations and analysis conducted, Liquid Pipelines designed using API 5L-X65 for the pipe material, Incolony 825 for CRA, 3LPP for the external corrosion coating material, with external corrosion thickness of 3 mm and a pipe wall thickness of 2,108 mm. Gas Pipelines designed using API 5L-X65 for the pipe material, Stainless steel 316 for CRA material, 3LPP for the external corrosion coating material, with an external corrosion coating thickness of 3 mm and a pipe wall thickness of 8.38 mm. Furthermore, for stability in the river area, it was found that the liquid pipe was stable when passing through the river, however the gas pipe was unstable under installation conditions, to prevent the instability, a cube-shaped concrete weight with 1 m ribs were placed at both ends of each pipe. In the analysis of thermal end expansion, the liquid pipeline virtual anchor point valued at 26,271 m and 135.44 m in the hydrotest condition and the operation condition with the expansion length of 2,237 mm and 59,205 mm in the hydrotest conditions and the operation condition. For the gas pipeline, the virtual anchor point valued at 64,948 m and 244,455 m in the hydrotest condition and the operation condition with the expansion length of 8,028 mm and 113,127 mm in the hydrotest conditions and the operation condition. Then, a stress analysis performed on the gas pipeline using the Ceasar II software resulted in smaller stress compared to the Allowable Stress, thus buckling will not occur. Finally, an upheaval buckling analysis conducted on the gas pipeline, showed that it began to fail when the imperfection height reaches 5.1 m.